Existence of Solution for Fractional Differential Problem with a Parameter (Communications in Mathematical Research, 2021)
We apply the method of lower and upper solutions combined with monotone iterations to fractional differential problem with a parameter. The existence ofminimal and maximal solutions is proved for the fractional differential problem witha parameter.
Keywords: Caputo derivative; parameter; monotone iterative method.